EFFECT OF RELATIONSHIP MARKETING ON CUSTOMER BEHAVIOUR IN GUARANTY TRUST BANK, ABUJA METROPOLIS - Abah, James Owi; Kassah, Virginia; Nanzing, Dannap E. (African Journal of Social and Behavioural Sciences, 2025)
In today’s competitive banking environment, relationship marketing has become essential for influencing customer behaviour. This study, therefore, examines the effect of relationship marketing on customer behaviour in Guaranty Trust Bank in Abuja Metropolis. The study adopted a survey research design, using primary data obtained from questionnaires distributed to a sample of 432 respondents. This sample is drawn from a population of 3,000,789. The research used various statistical tools such as correlation and regression analysis to test the hypotheses stated by the study in order to seek findings and draw conclusions. The research revealed that relationship marketing has a significant and positive effect on customer behaviour in GTB Abuja Metropolis. Specifically, the research found that the components of relationship marketing, such as trust and communication, have positive and significant effects on customer behaviour as regards loyalty in GTB Abuja Metropolis. The study, therefore, recommended that the management of GTB Abuja Metropolis should emphasize the various components of relationship marketing in order to affect the behaviour of their customers, especially as regards their loyalty.